(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Social media is an instrument that allows citizens to manage the political and economic resources within the government. However, on the other hand, it is the widespread use of social networks for their political purposes and the interference of social media in the political processes of the country that can become one of the big problems for national security. Such a phenomenon can also serve as a tool to destabilize the socio-political situation in the country during large-scale political processes, as was evident in October 2020 after the parliamentary elections in Kyrgyzstan. It is also impossible not to note the events that took place in Kazakhstan at the beginning of 2022. The power of social media can be truly incredible. It should be assumed that the power of social media in political processes in Kyrgyzstan is becoming an irreversible reality.